IMPLEMENTASI SISTEM PEMILIHAN GURU TERBAIK MENGGUNAKAN METODE SMART DAN BORDA BERBASIS WEBSITE - Choirun Nizar, Reza; Anita Andriani (Inovate, 2025)
Choosing the top educator serves as a recognition of the efforts of teachers who play a vital role in enhancing educational standards. The purpose of selecting the best teacher is to encourage motivation, dedication, responsibility, and professionalism among teachers. At SDN Blimbing, the process of selecting the best teacher is still done manually and uses only one assessment criterion, namely discipline. This causes the teacher selection process to be less objective and unstructured. As a solution to this problem, a web-based system for selecting the best teacher was designed by applying the SMART (Simple Multi Attribute Rating Technique) and BORDA methods. The SMART method is used to calculate the final score based on predetermined criteria, while the BORDA method is used to determine the teacher's ranking based on the voting results from several evaluators. The criteria used in this study include attendance, discipline, administrative completeness, teaching practice, and teaching obligations. The results of this study show that the developed system can simplify the teacher selection process automatically and produce objective teacher rankings. This system has also proven to improve accuracy and efficiency in decision-making. Based on data testing, the teacher with the highest ranking is Fitri Dwi Rahayu with a final score of 30.88, while the teacher with the lowest ranking is Hijrah Pua with a final score of 0.25.